A NOVEL POROUS MAGNESIUM PRODUCTION THROUGH POWDER METALLURGY TECHNIQUE USING WIRE-PIECES OF TITANIUM SPACE HOLDER FOR BONE SCAFFOLD MATERIALS - Sukmana, Shirley Savetlana, Yanuar Burhanudin, Mahruri Arif Wicaksono, Hadi Nur, Irza (University of Lampung, 2019)
Magnesium (Mg) and its alloys has a potential for the application for bone implant material as it?s biocompatibility and mechanical properties that fit to natural bone. Mechanical properties of magnesium alloy may close to human bone once it composed and produced in a specific production route. Mechanical properties of Mg alloy may close to cancelluos bone. Fabrication of porous magnesium for bone scaffold material aims to reduce the rigidity and strength of the material with density that can be adjusted to the original nature of the bone. It forms interconected porosity, has physical and mechanical properties similar to cancelluos bone. In this paper we describe the production and characterization of porous magnesium material for the potential application as bone scaffold through powder metallurgy technique with pieces of Titanium wire space holder. Mg containing titanium pieces then compacted and sintered before immersed in hydrofluoride acid solution to form a porous structure of magnesium. Density and porosity, micro vickers hardness, micro structure test was performed to prove the evidence of porous structure inside the Mg metal. This results finds a good cooperation and has a potential application for the fabrication of an inter-connected porous magnesium samples for cancellous bone implant.Keyword: Porous Magnesium, cancellous bone, implant, bone scaffold, titanium wire